Narrating the Soviet Era in Russian School History Textbooks - Konkka, Olga (London Taylor & Francis Ltd; Routledge, 2025)
Introduction: School History Textbooks: Mirrors of a Society Part 1: Russian History Textbooks for the Study of the Soviet Period 1. History Education and Textbooks in the USSR 2. Between Innovation and Path Dependency (1992-2000) 3. Government Interventionism or a Search for a Consensus? (2001-2012) 4. Introducing the Unified History Textbooks (2013-2022) Part 2: The Soviet Era in Post-Soviet Russian History Textbooks 5. How the First Soviet Decade Was Presented in Post-Soviet Russian History Textbooks 6. Stakes and Costs of Modernization : The Stalin Era as Portrayed in Post-Soviet Russian History Textbooks
E-Book / Zugriff nur im Lesesaal
Keywords: 1992-2021; 1917-1991; Geschichtsbuch; Lehrbuch; Sowjetunion; Russland